Perancangan Motion Graphic Bangga Kecantikan Lokal (Indonesia) Kepada Remaja Putri Usia 18-22 Tahun di Indonesia - Prastiti Setya Adiningsih; Bintang Pramudya Putra Prasetia (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2022)
Beauty is one of important factors that affects the life of every woman. In Indonesia, more than 90% of Indonesian women say that beauty has a big effect on their lives, such as social life, work, popularity, and also the chance to attract others. Beauty standards are always changing every decades to fit the new public taste of the majority, and beauty standards in Indonesia isn’t an exception. Therefore, a motion graphic video design was made to educate the public, especially women in Indonesia, to understand deeply about beauty standards and always participate in maintaining Indonesian beauty.